Laboratory assessment of systemic lupus erythematosus: Review article - Alhussain, Ali Hassan; Alquwayi, Waseem Ali; Alkuwaiti, Yasser Abdrab Alameer; Almehainy, Ahmed Mohammed; Alkhathami, ‏Adel Ahmed (International journal of health sciences, 2020)
Background: Systemic lupus erythematosus (SLE) is a multifaceted autoimmune disorder characterized by the production of autoantibodies and immune complexes, which play essential roles in its pathogenesis, diagnosis, and classification. Recent classification criteria emphasize the inflammatory nature of SLE, which is critical for assessing disease activity. Aim: This review article aims to evaluate the laboratory assessments utilized in diagnosing and monitoring SLE, with a specific focus on serological markers and their relation to inflammatory processes. Methods: A comprehensive review of current literature on SLE laboratory assessments, including serological markers such as autoantibodies, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP), was conducted. Additionally, recent classification criteria from EULAR and ACR were analyzed to determine their implications for understanding SLE activity and inflammation. Results: The review found that inflammatory markers, particularly ESR, correlate with disease activity in SLE, while CRP levels may indicate bacterial infection rather than SLE activity. Furthermore, pro-inflammatory cytokines significantly contribute to the inflammatory manifestations seen in SLE. Conclusion: Laboratory assessments for SLE should emphasize inflammatory markers to enhance disease management. Integrating these markers with clinical features will improve diagnostic accuracy and provide a better understanding of SLE's inflammatory underpinnings.